Lithium halide coating as an effective intergrain engineering for garnet-type solid electrolytes avoiding high temperature sintering. (1st November 2018) - Zhang, Zhaoshuai; Zhang, Long; Yu, Chuang; Yan, Xinlin; Xu, Bo; Wang, Li-min
Abstract: Garnet-type Li7 La3 Zr2 O12 solid electrolytes were commonly prepared by two steps solid-state reaction method, which undergoes high temperature over 1000 °C and thus inevitable for lithium volatilization and formation of secondary phases. Here, we propose a new intergrain architecture engineering of a solution method, to avoid high temperature sintering for preparing lithium halide (LiX) coated garnet-type solid electrolytes, which contain Al and Ta co-doped Li7 La3 Zr2 O12 (Li6.75 La3 Zr1.75 Ta0.25 O12, LLZTO) synthesized at 900 °C with cubic structure. Owing to the increased relative density, the improved formability, and the altered ion transport mode from point to face conduction by LiX coating on LLZTO grains, LiX-coated LLZTO samples demonstrate a good Li dendrite suppression ability and a high ionic conductivity that is three orders of magnitude higher than pristine LLZTO. In another way, this result demonstrates the critical role of the grain boundaries on the ion transport for oxide superionic conductors. The present coating method provides a new strategy to prepare brittle solid electrolytes avoiding high temperature sintering. Graphical abstract: